2017
DOI: 10.1002/jcp.26171
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of miR‐216b: Prognostic and predictive value in acute myeloid leukemia

Abstract: Accumulating studies have shown that miR-216b acted as a tumor suppressor and was down-regulated in solid tumors. However, little studies revealed the role or clinical implication of miR-216b in blood cancers. Herein, we reported miR-216b expression and its clinical significance in patients with acute myeloid leukemia (AML). In the current study, we analyzed bone marrow (BM) miR-216b expression in 115 de novo AML patients examined by real-time quantitative PCR. Notably, BM miR-216b expression was significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Overexpression of miR-217 inhibited cellular proliferation and enhanced cell chemosensitivity to doxorubicin by the cell apoptosis pathway in AML cells (17). Some studies have clarified the potential roles of miRNAs as diagnostic and prognostic biomarkers in leukemia (18). For example, Li et al showed that increased expression of miR-181a or miR-181b was significantly associated with longer overall survival (OS) in AML patients (19).…”
mentioning
confidence: 99%
“…Overexpression of miR-217 inhibited cellular proliferation and enhanced cell chemosensitivity to doxorubicin by the cell apoptosis pathway in AML cells (17). Some studies have clarified the potential roles of miRNAs as diagnostic and prognostic biomarkers in leukemia (18). For example, Li et al showed that increased expression of miR-181a or miR-181b was significantly associated with longer overall survival (OS) in AML patients (19).…”
mentioning
confidence: 99%
“…These findings suggested that measuring miRNA may have potential advantages for predicting prognosis of AML compared to assessed gene mutations such as DMNT3A, FLT3-ITD, NPM1, and CEBPA. In published studies, univariate and multivariate analysis showed that miR-98, miR-99a, miR-340, miR-216b, and miR-34c had independent stronger prognostic impact on EFS and OS (P < 0.05) than gene mutations in FLT3-ITD, NPM1, DMNT3A, RUNX1, CEBPA, and TP53 [80,81,85,86].…”
Section: Micrornas As Biomarkers For Prognosis In Acute Myeloid Leukemiamentioning
confidence: 99%
“…Mounting studies have shown that miRNAs can be used to predict outcome in CN-AML. Zhang et al reported miR-216b overexpression as an independently poor prognostic factor for CN-AML and may provide a valuable biomarker associated with disease recurrence in AML [65]. In 224 patients with CN-AML, high miR-362-5p expression was associated with older age and shorter OS compared with low expressers [66].…”
Section: Micrornas As Biomarkers For Prognosis In Acute Myeloid Leukemiamentioning
confidence: 99%
“…miRNAs have many properties of good AML prognostic biomarkers, such as wide presence in various tissues, highly conserved sequences, and easy and sensitive detection, as well as stability under extreme conditions [8]. Mounting studies have shown that miRNAs can be used to predict outcome in CN-AML.…”
Section: Introductionmentioning
confidence: 99%